2016
DOI: 10.1371/journal.pone.0163989
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence of Salmonella in Australia, 2000-2013

Abstract: Salmonella is a key cause of foodborne gastroenteritis in Australia and case numbers are increasing. We used negative binomial regression to analyze national surveillance data for 2000–2013, for Salmonella Typhimurium and non-Typhimurium Salmonella serovars. We estimated incidence rate ratios adjusted for sex and age to show trends over time. Almost all states and territories had significantly increasing trends of reported infection for S. Typhimurium, with states and territories reporting annual increases as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 20 publications
4
55
4
Order By: Relevance
“…Without this evidence, it is difficult to compare whether the food vehicles that cause outbreaks identified in this study are the same as those that cause sporadic illness. Also, while individual risk factors, such as age and sex, have been identified to be important risk factors for sporadic illness in Australia (Ford et al, 2016), in this study, there was little difference in demographic characteristics of cases in foodborne or suspected foodborne S. Typhimurium and non-Typhimurium Salmonella outbreaks. This suggests that the individual risk factors of age and sex are not as important in outbreaks as they are with sporadic illness.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Without this evidence, it is difficult to compare whether the food vehicles that cause outbreaks identified in this study are the same as those that cause sporadic illness. Also, while individual risk factors, such as age and sex, have been identified to be important risk factors for sporadic illness in Australia (Ford et al, 2016), in this study, there was little difference in demographic characteristics of cases in foodborne or suspected foodborne S. Typhimurium and non-Typhimurium Salmonella outbreaks. This suggests that the individual risk factors of age and sex are not as important in outbreaks as they are with sporadic illness.…”
Section: Discussioncontrasting
confidence: 50%
“…The increasing trend of outbreaks in Australia, together with comparatively high and increasing Salmonella spp. notification rates (Ford et al, 2016), emphasizes the continued importance of identifying food vehicles in outbreaks and implementing control strategies throughout the food chain to prevent illness.…”
Section: Discussionmentioning
confidence: 99%
“…The northern states of Australia consistently report higher rates of salmonellosis than the national average [3]. A case-control study of young children in tropical Australia found widespread Salmonella contamination in households, with environmental transmission identified as the most likely cause of illness [10].…”
Section: Introductionmentioning
confidence: 99%
“…The continuous emergence of multidrug-resistant strains of non-typhoidal Salmonella constitutes a serious health hazard globally. In recent years, enteric Salmonella enterica associated with gastrointestinal infection in humans has been reported with increasing frequency worldwide [1].…”
Section: Introductionmentioning
confidence: 99%